2022
DOI: 10.3390/polym14193929
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fiber Volume in Hybrid Short Glass/Cellulose Reinforced Thermoplastic Compounds

Abstract: Glass fibers (GF) and regenerated cellulose fibers (RCF) are possible partners in the hybrid reinforcement of thermoplastics because of their different properties. Due to the weak bonding properties of polypropylene, coupling agents are used and the fiber volume content is set high to achieve high reinforcing effects. A lower fiber content of GF can raise the toughness properties of a reinforced polypropylene which is investigated in this study with different ratios of GF and RCF. The composites are tested in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…All four samples showed fiber pull-out holes and fiber breakage with distance as well as directly on the surface. As Zarges et al [ 36 ] and Kahl et al [ 37 ] have already observed, the fibers stuck straight out of the surface. That indicates that the fiber orientation proceeds in the direction of loading during the injection molding process.…”
Section: Resultsmentioning
confidence: 74%
“…All four samples showed fiber pull-out holes and fiber breakage with distance as well as directly on the surface. As Zarges et al [ 36 ] and Kahl et al [ 37 ] have already observed, the fibers stuck straight out of the surface. That indicates that the fiber orientation proceeds in the direction of loading during the injection molding process.…”
Section: Resultsmentioning
confidence: 74%
“…The screw design is shown in Figure 1 . The screw configuration was optimized in collaboration with Leistritz and used in processing in previous studies [ 14 , 33 , 52 ] for cellulose-based composites. The granules (feeding zone) and fibers (Zone 3) were fed by a gravimetric feeding system.…”
Section: Methodsmentioning
confidence: 99%
“…Using the following formula, the response factor ( R f ) can first be calculated. The response factor results from the quotient of the absolute mass (in μg) of toluene and the resulting peak areas [ 52 ]: …”
Section: Methodsmentioning
confidence: 99%